SURFACE QUALITY OF THE Ni-TiO2 COMPOSITE COATINGS PRODUCED BY ELECTROPLATING - Stanković, Velizar; Gojo, Miroslav; Grekulovic, Vesna; Pajkić, Ninoslav; Cigula, Tomislav (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Composite nickel coatings onto brass substrate were produced from suspensions consisted of a conventional nickel sulphate bath and fine TiO2 particles (dp < 0.35 µm). Characterization of coatings surface was performed by using optical and SEM micrographs, by EDX analysis and by determining the surface roughness parameters. Metallographic analysis has also been done in order to get an insight about particles distribution inside the coating thickness. Presence of TiO2 particles in electrodeposited metal affected the surface morphology. Particles were embedded as smaller or bigger agglomerates within the coatings, as well as the individual particles. Metallographic analysis showed uniform distribution of particles and their agglomerates within the coating. Surface roughness parameters of the composites have had up to 35 times higher values than the ones of the pure nickel coatings. Roughness maxima appeared at particles concentration between 10 and 20 g dm-3. Then it drops down and remains constant for concentrations > 40 gdm-3. SEM micrographs showed irregularities like single-, or beads of nodules on the surface. Relationship between surface roughness and current density has not been noted.